Influence of Upper and Lower Body Adipose Tissue on Insulin Sensitivity in South Asian Men. (1st October 2012) - Balakrishnan, Preetha; Grundy, Scott M.; Islam, Arsalla; Dunn, Fredrick; Vega, Gloria Lena
Abstract : Background: South Asians have a high prevalence of insulin resistance, which predisposes to type 2 diabetes. Rationale: In the current study, we examined whether insulin sensitivity in South Asian men and men of European descent (Europids) relates to truncal and lower body fat, number of adipocytes, and cell size distribution. Results: Fifteen South Asian men and 15 Europid young men with comparable body mass indexes completed assessments of insulin sensitivity, body composition analysis by dual-energy x-ray absorptiometry, and measurement of adipocyte cellularity in the subcutaneous abdominal (truncal) and gluteal (lower body) adipose tissue. The South Asians and the Europids had similar total body fat and fat contents in truncal and lower body regions. Compared to the Europids, the South Asians had a greater insulin resistance shown by fasting insulin, area-under-the-curve for postprandial insulin, oral glucose insulin sensitivity, homeostatic model assessment of insulin resistance, β-cell index, and triglyceride-to-high-density lipoprotein ratio. The South Asians had similar number of adipocytes to the Europids, but the South Asians had significantly higher ratios of small-to-larger adipocytes. The South Asians further had a higher fraction of very large adipocytes. In both South Asians and Europids, truncal fat was positively associated with insulin resistance. In the South Asians but not in the Europids, lower body fat was associated with severity of insulin resistance. Conclusions: The results suggest first, a higher ratio of small-to-larger adipocytes in the South Asians consistent with a lesser lipid storage capacity of adipose tissue; and second, the positive association of lower body fat with insulin resistance in the South Asians implies that fat in their lower body worsens insulin resistance. This association was not observed in the Europids.